2020
DOI: 10.1002/wer.1283
|View full text |Cite
|
Sign up to set email alerts
|

Sequential synergetic sorption analysis of Gracilaria Rhodophyta biochar toward aluminum and fluoride: A statistical optimization approach

Abstract: The present work proposes the synthesis of robust biochar from Gracilaria Rhodophyta red weeds for sequential removal of Al(III) and fluoride from wastewater. The sorption experiments have been modeled by preliminary optimization of operational parameters using 2 4 factorial statistical modeling. The model has estimated an optimum sequential synergetic removal of 44.5 mg/g of Al(III) and 2.1 mg/g of fluoride onto the biochar. FESEM, BET, XRD, EDX, and FTIR established the potentiality of biochar toward synerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…48 The two peaks at 1635 cm −1 and 1060 cm −1 are attributed to the stretching vibration of the aromatic ring CC and the stretching vibration of C–H, respectively, indicating that these biochars generated carbon with an aromatic structure. 49,50 Fourier transform infrared spectroscopy analysis showed that the composition of SRBC and Mn/SRBC biochar before and after KMnO 4 modification was similar, but the number of functional groups was significantly different, which led to the difference in the intensity of their absorption peaks. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…48 The two peaks at 1635 cm −1 and 1060 cm −1 are attributed to the stretching vibration of the aromatic ring CC and the stretching vibration of C–H, respectively, indicating that these biochars generated carbon with an aromatic structure. 49,50 Fourier transform infrared spectroscopy analysis showed that the composition of SRBC and Mn/SRBC biochar before and after KMnO 4 modification was similar, but the number of functional groups was significantly different, which led to the difference in the intensity of their absorption peaks. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…X-ray diffraction analysis: XRD spectrum analysis is an essential means to study the crystalline structure of substances (Naga Babu et al 2020). The crystal structure characteristics of SRBC500 biochar prepared at different pyrolysis times were analyzed by X-ray technology, as shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, biochar prepared by hydrothermal pyrolysis below 573 K is rich in oxygen-containing functional groups (-COOH, -OH, etc.) and has stronger ion exchange capacity ( Naga Babu et al, 2020 ). As the pyrolysis temperature increases, the abundance of hydroxyl, amino, and carboxyl groups decrease and the degree of carbonation increases ( Kumar et al, 2020 ).…”
Section: Conventional Types Of Adsorbentsmentioning
confidence: 99%